Intervensi Ruang Redaksi Media Televisi Lokal Metro News Jateng-DIY - septi wulandari; Sunarto (Kalijaga Journal of Communication, 2022)
The newsroom is a place to control news in a mass media. From that room, the editor-in-chief and the editors become important controls to direct the journalists. All editorial crews work with a journalistic code of ethics that is inherent in the profession as a journalist so that it provides various limitations, let alone interferes with independence at work. This study tries to explore the newsroom (newsroom) of Central Java-DIY Metro TV when producing news programs and the various interventions they face. This study uses media political economy theory in a critical paradigm, this study focuses on the structuration process that occurs in the Metro TV newsroom, Central Java-DIY. This study uses an intrinsic case study in a descriptive-qualitative approach. The results showed that there were internal and external interventions in the newsroom. Internal intervention comes from the media business division and external intervention comes from sources within the local government. The editors take measurable actions to respond to all these interventions.